Iraq - Augustin, Byron; Kubena, Jake, 1982- (New York : Children's Press, 2006)
Discusses the geography and climate, history, wildlife, economy, government, people, religion, and culture of Iraq.
Cradle of civilization -- Seserts, rivers, and mountains -- A struggle to survive -- Reflections in time -- The birth of democracy -- Black gold -- A diverse population -- A Muslim nation -- A rich culture -- Hope for the future.
Includes bibliographical references (p. 134) and index.
Keywords: Iraq -- Juvenile literature; Iraq